Ketersediaan Sumber Sejarah pada Museum Adityawarman yang Relevan dengan Pembelajaran di SMA - Smaysa Smaysa; Zafri Zafri (Jurusan Sejarah FIS UNP, 2023)
The use of museums as a source for studying history can add broad insights for students. One example is making the museum collection a source of study. The museum collection is supposed to be used to add information, insights, and to increase interest in studying history. The study is a qualitative description that aims to identify the availability of museum Adityawarman history sources. The object in this study is a historical or museum collection. Some historical sources in museums include libraries, sites/temples, relics, textbooks, encyclopedias, the Internet, maps, atlas, newspapers, historical dictionaries, archives, historiography works, and other written sources. The museum’s mollection of relics of ancient human life, the roots of Indonesian ancestors, of pre-racial cultures, and of object during the colonization of Europe.